Zika and aedes aegypti: New and old challenges (2017)
Infection with the zika virus had a great impact not only on pregnant women and newborns, but also on public health, on popular ideas about Aedes aegypti and with respect to women’s social rights. The objective of this paper is to identify this impact and the historical, social and health changes of the disease and the legacy of the zika virus. Interventions by researchers from different specialties foster conditions for more comprehensive investigations into future epidemic threats in Brazil and Latin America. This dialogue took place after the seminar “Aedes aegypti: past and future health emergencies,” organized by the Casa de Oswaldo Cruz, when we talked with some speakers and other leading researchers about the history and challenges of Aedes aegypti and zika. © 2017, Fundacao Oswaldo Cruz. All rights reserved.